Pengaruh Variasi Tekanan Kompaksi dan Fraksi Penguat terhadap sifat kekerasan dan densitas pada Karakteristik AMC - sukanto, sukanto "-" (TURBO [Tulisan Riset Berbasis Online], 2025)
The use of asbestos in the production of brake pads is known to pose health risks, necessitating environmentally friendly innovations. This study aims to evaluate the effects of the percentage of reinforcement and hot compaction pressure on the density and hardness properties. Composites were produced using the powder metallurgy method, which involves grinding recycled aluminum powder, silica sand, and boiler fly ash with a ball mill. The process parameters used were a Ball Powder Weight Ratio (BPR) of 10:1, a rotation speed of 90 rpm, and a grinding time of 6 hours, with varying reinforcement percentages of 8%, 12%, and 16%. The compaction process was performed using bidirectional pressing with varying pressures of 5000, 5400, and 5800 PSI at a temperature of 350°C, with a holding time of 10 minutes. The sintering process was conducted at a temperature of 600°C with a holding time of 10 minutes. Testing was carried out using density tests in accordance with ASTM B962-17 and portable Brinell hardness tests in accordance with ASTM E110-14. The test results showed that an increase in the percentage of reinforcement and hot compaction pressure improved the density and hardness of the composite. The highest density obtained was 2.262 g/cm³, while the highest hardness reached 49.2 HB at a reinforcement percentage of 16% with a compaction pressure of 5800 PSI.